2012
DOI: 10.1103/physrevlett.108.185303
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Anomaly, Universal Relations, and Breathing Mode of a Two-Dimensional Fermi Gas

Abstract: In this Letter, we show that the classical SO(2,1) symmetry of a harmonically trapped Fermi gas in two dimensions is broken by quantum effects. The anomalous correction to the symmetry algebra is given by a two-body operator that is well known as the contact. Taking into account this modification, we are able to derive the virial theorem for the system and a universal relation for the pressure of a homogeneous gas. The existence of an undamped breathing mode is associated with the classical symmetry. We provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 45 publications
3
85
1
Order By: Relevance
“…Universal contact relations should also hold in this case [6,[17][18][19][20]. Interestingly, a recent experiment [21] has found that the monopole breathing mode is essentially undamped and has no interaction-dependent shift [22][23][24]. This implies a scale invariance in the system [25] that has also been observed in weakly interacting 2D Bose gases [26].…”
Section: Introductionmentioning
confidence: 84%
“…Universal contact relations should also hold in this case [6,[17][18][19][20]. Interestingly, a recent experiment [21] has found that the monopole breathing mode is essentially undamped and has no interaction-dependent shift [22][23][24]. This implies a scale invariance in the system [25] that has also been observed in weakly interacting 2D Bose gases [26].…”
Section: Introductionmentioning
confidence: 84%
“…However, the true inter-atomic interactions break the scaling invariance, and this leads to the frequency shift of breathing modes. In two-component Fermi gas with s-wave interactions, one finds that this shift is related to the contact of the system [38,39], and in particular, at unitarity, the scaling invariance is regained [40]. However, quite differently for a single component Fermi gas with p-wave interaction in two dimensions, the scaling invariance is also broken even at resonance when a → ∞ due to the existence of the contact C R .…”
Section: Breathing Mode and Contactsmentioning
confidence: 94%
“…The possibility of measuring the effects of quantum anomalies in nonrelativistic systems has prompted the development of quantum-field-theoretical approaches in the mathematical description of such anomalies [1][2][3][4][5]. In particular, we have recently developed a path-integral, Fujikawa approach to the calculation of anomalous corrections to virial theorems and equations of state for systems with a classical SO(2, 1) symmetry [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%